2012
DOI: 10.1111/j.1742-1241.2012.02986.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache in essential thrombocythaemia

Abstract: Headache is frequently reported as one of the neurological manifestations of essential thrombocythaemia (ET) and other myeloproliferative neoplasms. It is associated with considerable morbidity; yet, it is a frequently under-recognised symptom. In patients with ET, headaches may be attributable to the disease, to the prescribed ET treatment, or unrelated to ET. The majority of headaches in ET are self-limiting and can be managed with standard headache therapies such as paracetamol, but it is vital that the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
(90 reference statements)
1
16
0
2
Order By: Relevance
“…Chronic brain ischemia often manifests itself with headache and/or asthenia [ 7 ]. There exists a firm link between hematological characteristics and cephalgia, supported by several studies [ 8 , 9 ] where it has been demonstrated that in PV and ET, headache is often a first symptom of Ph-MPD [ 10 ]. Our findings confirm these data, with as much as 70% of patients referring to their physician with headache as the main complaint (which preceded the diagnosis of Ph-MPD).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic brain ischemia often manifests itself with headache and/or asthenia [ 7 ]. There exists a firm link between hematological characteristics and cephalgia, supported by several studies [ 8 , 9 ] where it has been demonstrated that in PV and ET, headache is often a first symptom of Ph-MPD [ 10 ]. Our findings confirm these data, with as much as 70% of patients referring to their physician with headache as the main complaint (which preceded the diagnosis of Ph-MPD).…”
Section: Discussionmentioning
confidence: 99%
“…The association of JAK2 V617F -mutated thrombocythemia in ET and PV patients who have a high risk of aspirin-responsive platelet thrombophilia with a broad spectrum of microvascular circulation disturbances including erythromelalgic ischemic complications and MIAs is being increasingly recognized (fig. 4) [23,24,25,26]. Similar to the platelet-mediated arteriolar painful thrombotic and inflammatory processes that occur in the peripheral and cerebral endarterial circulation (erythromelalgia and MIAs), this thrombocythemia also occurs in the coronary (acute coronary syndromes) and liver circulation (Budd-Chiari syndrome), the adrenal microcirculation and the microcirculation of the skin of the legs and arms (superficial thromboangiitis) [1,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…This broad spectrum of microvascular circulation disturbances and the subsequent major thrombotic complications have been observed in JAK2 V617F - and MPL 515 -mutated thrombocythemia and in JAK2 wild type thrombocythemia [23,24]. If the disturbances are not recognized due to unfamiliarity with thrombocythemia-specific manifestations, and when treatment with aspirin is not received, ET and PV patients are at very high risk of major arterial thrombosis including TIAs, stroke, angina pectoris, myocardial infarction and digital gangrene [23,24,25,26,27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Por este motivo se ha propuesto en la práctica clínica, que los pacientes que inician los episodios de cefalea en relación temporal con el diagnóstico de TE y si éstos episodios se resuelven en el espacio de tres meses de tratamiento con dosis bajas de Ácido acetil salicílico (AAS) o terapia citoreductora, entonces puede considerarse la cefalea como manifestación de la TE (15).…”
Section: Introduccionunclassified